Correction: Al Madhoun et al. Randomized Clinical Trial: Bone Bioactive Liquid Improves Implant Stability and Osseointegration. J. Funct. Biomater. 2024, 15, 293 - Ashraf Al Madhoun; Khaled Meshal; Neus Carrió; Eduard Ferrés-Amat; Elvira Ferrés-Amat; Miguel Barajas; Ana Leticia Jiménez-Escobar; Areej Said Al-Madhoun; Alaa Saber; Yazan Abou Alsamen; Carles Marti; Maher Atari (Journal of Functional Biomaterials)
Error in Figure and Figure Legend [...]